(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research aims to show the relationship between artificial intelligence in accounting education and its role in achieving sustainable development goals in the Kingdom of Bahrain. The research dealt with the role of artificial intelligence applications in accounting education at the University of Applied Sciences as a model for Bahraini universities to achieve sustainable development goals. The application of artificial intelligence in accounting education achieves seven of the seventeen sustainable development goals. It also concludes that there is an artificial intelligence infrastructure in the Kingdom of Bahrain, as it occupies a leading regional position in digital transformation, as Bahrain ranks first in the Arab world in the ICT development index and the fourth globally, and the research recommends Presenting a proposed strategy for artificial intelligence that includes achieving the goals of Bahrain’s Vision 2030. The research also recommends the creation of the Ministry of Artificial Intelligence, the formation of the State’s Artificial Intelligence Council, the establishment of a working group with CEOs for innovation in government agencies, and the formulation of strategic plans for artificial intelligence at the level of sectors and ministries. Finally, the research recommends the development of master’s and phd graduate programs in artificial intelligence.